Variability for Glutenins, Gluten Quality, Iron, Zinc and Phytic Acid in a Set of One Hundred and Fifty-Eight Common Wheat Landraces from Iran - Zahra Maryami; Ana Belén Huertas-García; Mohammad Reza Azimi; Nayelli Hernández-Espinosa; Thomas Payne; Fausto Cervantes; Velu Govindan; Maria Itria Ibba; Carlos Guzman (Agronomy, 2020)
Bread wheat can be used to make different products thanks to the presence of gluten, a protein network that confers unique visco-elastic properties to wheat doughs. Gluten is composed by gliadins and glutenins. The glutenins can be further divided into high and low-molecular-weight glutenins (HMWGs and LMWGs, respectively) and are encoded by Glu-1 and Glu-3 loci. The variability of these genes is associated with differences in quality. Because of this, the identification of novel glutenin alleles is still an important target. In this study, 57 haplotypes or glutenin combinations were registered among a set of 158 Iranian landraces and five novel HMWGs alleles were identified. The landraces were also characterized for several quality traits, including gluten quality, which allowed to associate the different glutenin alleles with low or high quality. Other quality traits examined were iron, zinc, and phytate contents, which are intimately related with the nutritional quality. Important variation for these components was found as well as for the phytate:iron/zinc molar ratios (related to the potential bioavailability of these important micronutrients). The landraces identified in the present study (some of them combining high gluten quality with low phytate:zinc values) could be a useful resource for breeders who aim to improve the wheat end-use quality and especially the content of zinc and its relative bioavailability.